KAJIAN UNDANG-UNDANG OTONOMI DAERAH TERHADAP PERSOALAN BATAS WILAYAH - Abdul Choliq Dahlan (Jurnal Hukum, 2012)
Regional autonomy laws either to Act No. 22 of 1999 Article 89 and instead of Act No. 32 of 2004 still contains many weaknesses that ultimately caused many disputes issues between regions, especially specifically raises the issue boundaries. Thus certainly needed a legal product that is able to provide the answers and be able to prevent the emergence of inter-regional disputes, in this case the writer tend to choose in the form of laws rather than of laws under the Act because the problems that arise boundaries often cause much issues such as politics, economics, culture, religion, race and so forth.From the Nurbadri findings is achieved the important point that boundaries conflict between regions mainly influenced by the legal and non-legal factors. Legal factor consist ofÂ  2 (two): first law of substance caused by the formation of legislation that are too hasty, blurring the setting of boundaries, and the second, lack of socialization regional expansion law. Next is a legal structure is still obscure because of the change laws that are too short.Non-legal factors, the socio-cultural, economic, political and service approach. In order settlement boundaries to do with two approaches: first, the legal settlement can be reached through completion using region Autonomy and by the formation of legislation and settlement through the Constitutional Court, non-legal settlement, the first can be done through settlement discussions in which can be by way of consultation, negotiation, mediation, as stipulated in the Arbitration Law, as a way to find a solution for resolving regions boundaries conflict.Secondly, the inter-regional cooperation as specified in Article 195 of Law No. 32 of 2004. Third, socio-cultural approach as a step resolution by exploring indigenous cultures as to marriage (marriage custom) by mating two cultures, those are the local communities culture with immigrant communities (not native) as a measure to reduce border conflicts.Keywords: Law, Autonomy, Boundaries